Mapping Basketball Research in Physical Education and Sport Sciences: A Systematic Literature Review - Imanuddin Siregar; Joko Priono; Arief Rahman (INSPIREE: Indonesian Sport Innovation Review, 2026)
The  purpose  of  the study. This study aimed to systematically map the development, thematic orientation, and methodological evolution of basketball research within physical education and sport sciences during 2015–2025, while identifying research gaps and future directions. Materials and methods. A PRISMA-guided systematic literature review was conducted using searches across Scopus, Web of Science, PubMed, ERIC, SPORTDiscus, Google Scholar, and selected Indonesian university repositories (January 2015–December 2025). Eligibility criteria prioritized peer-reviewed articles and high-quality theses with clear methodologies and explicit educational/pedagogical relevance. Data were extracted using a standardized form (e.g., context, participants, design, theoretical framing, thematic focus, and key findings). Quantitative synthesis used bibliometric analysis and VOSviewer network mapping, while qualitative synthesis applied content analysis (deductive–inductive coding). Findings were integrated through a convergent mixed synthesis approach. Results. The search identified 8,764 records; after duplicate removal, 6,412 records were screened. A total of 1,247 studies were included for bibliometric analysis, and 89 studies met criteria for in-depth qualitative synthesis. Quantitative designs dominated (64.2%), followed by qualitative (17.6%), mixed methods (16.9%), and review-based studies (1.3%). The synthesis revealed six major thematic clusters: technical skill development, pedagogical innovation, biomechanical performance analysis, psychological factors, technology-based learning, and program evaluation/assessment. Overall trends indicate a shift from performance-focused traditions toward learner-centered, evidence-based, technology-supported, and context-sensitive research, including notable contributions from Indonesia (8.9% of included studies). Conclusions. Basketball research in physical education and sport sciences expanded substantially from 2015–2025 and matured into a more holistic and methodologically plural field. Future research should strengthen cross-cultural representation, refine standardized outcome measures, and increase implementation-focused studies that account for contextual constraints (e.g., resources, teacher capacity, and cultural norms).